Earthquake Shocks Around Delhi-NCR and the Adjoining Himalayan Front: A Seismotectonic Perspective - Khan, Prosanta Kumar; Mohanty, Sarada P.; Chakraborty, Partha P.; Singh, Rashmi (Frontiers in Earth Science, 2021)
An increase in the number of earthquakes and subsequent clustering in northwest India, particularly around the Delhi-National Capital Region (NCR) and adjacent NW Himalayan front, provides a good opportunity to understand the underpinning tectonic controls and the likelihood of any large earthquake in the future. The 2001 Mw 7.7 Bhuj, 2011 Mw 6.9 Sikkim and 2015 Mw 7.8 and 7.3Nepal earthquakes (and2004 Mw 9.2 Sumatra event) are important in this context. We analysed the seismicity around the Delhi-NCR and the adjoining Himalayan front, including event clustering and the spatio-temporal distribution of b-values, in the context of kinematics and the regional geodynamics. The overall moderate-to-low b-values, both in time and space, since 2016 provide information regarding an increase and subsequent stabilisation of the stress field in the study area. The analysis led to the identification of (i) a structurally guided stress field in the region between the Kachchh and the NW Himalaya that coincides with the direction of Indian plate convergence and (ii) frequent occurrences of earthquakes particularly in the Delhi, Kangra and Uttarkashi areas. We propose that faults in western Peninsular India, which pass through the margins of the Aravalli Range and the Marwar basin, the isostatically over-compensated Indo-Gangetic Plains beneath the Delhi and the Himalayan foothills of the under-plated Indian lithosphere, act as stress guides, concentrating and increasing stress in regions of lithospheric flexure. This enhanced stress may trigger a large earthquake.